Quantitative analysis of chives irrigated with saline water - Da Silva, Patrícia Ferreira; Cavalcante, Valéria Santos [UNESP]; Dos Santos, Jania Claúdia Camilo; Costa, Elenize Silva; Barbosa, Josefa Tatiana Vieira (My University, 2014)
The common chives (Allium fistulosum) is one of the vegetables most produced in the Alagoas state, being cultivated by small farmers. However, the cultivation of this vegetable in the region suffers serious problems with the poor quality of irrigation water. In this sense, the objective was to evaluate the growth Allium fistulosum irrigated with different salinity levels of irrigation water. In an experiment conducted under field condition in campus of the Federal University of Alagoas - Arapiraca. The treatments were five levels of electrical conductivity (S1: 0.7, S2: 1.4, S3: 2.1; S4: 2.8; S5: 3.5 dS m-1). The maximum performance for the variables root dry mass, total dry mass of root, root length, number of bulbs, fresh mass of the root and relation root:aerial part was obtained with approximately 2.00 dS m-1 at 15 days after transplantation. Variables root dry mass, total dry mass of root, fresh mass of root, root growth, bottom diameter of the bulb and the relation root:aerial part at 30 days after transplantation had a linear decrease reduction from 0.7 dS m-1.
Análise quantitativa da cebolinha irrigada com água salina
Keywords: Allium fistulosum; Electrical Conductivity; Water Quality; Yield